2020
DOI: 10.3389/fphar.2020.00094
|View full text |Cite
|
Sign up to set email alerts
|

Perindopril Improves Cardiac Function by Enhancing the Expression of SIRT3 and PGC-1α in a Rat Model of Isoproterenol-Induced Cardiomyopathy

Abstract: Mitochondrial biosynthesis regulated by the PGC-1a-NRF1-TFAM pathway is considered a novel potential therapeutic target to treat heart failure (HF). Perindopril (PER) is an angiotensin-converting enzyme inhibitor that has proven efficacy in the prevention of HF; however, its mechanism is not well established. In this study, to investigate the mechanisms of PER in cardiac protection, a rat model of cardiomyopathy was established by continuous isoproterenol (ISO) stimulation. Changes in the body weight, heart we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…A previous study noted that increased ATP production in myocardial tissues was correlated with improved functioning of the mitochondrial respiratory chain. 18 Similarly, amplified secretion of chemokine has also been was observed at the site of infection in polymicrobial sepsis, while TLR2 silencing brought about a decrease in chemokine production in our findings. 19 Interestingly, a previously conducted report has indicated that LPS treatment at certain doses brings about marked elevations in the expression of TLR2 at both mRNA and protein levels in rat kidney epithelial cells.…”
Section: Discussionsupporting
confidence: 84%
“…A previous study noted that increased ATP production in myocardial tissues was correlated with improved functioning of the mitochondrial respiratory chain. 18 Similarly, amplified secretion of chemokine has also been was observed at the site of infection in polymicrobial sepsis, while TLR2 silencing brought about a decrease in chemokine production in our findings. 19 Interestingly, a previously conducted report has indicated that LPS treatment at certain doses brings about marked elevations in the expression of TLR2 at both mRNA and protein levels in rat kidney epithelial cells.…”
Section: Discussionsupporting
confidence: 84%
“…Meanwhile, the ISO-induced HF group was given a subcutaneous injection of ISO (Purity 98%) at 10 mg/kg/d. The infusion was consecutive in the preceding two weeks (Zhu et al, 2020). Afterward, the survived rats in the ISO-induced HF group were further randomly divided into ISO (n = 10) and ISO +TMZ group (n =10).…”
Section: Animal Model and Treatment Protocolsmentioning
confidence: 99%
“…In the present study, perindopril administration to DSS-treated mice was associated with a significant increase in the levels of Nrf2 and the antioxidant enzymes, together with a significant decrement in iNOS and ROS levels when compared to mice treated with DSS alone. This may be explained by the findings of Zhu et al [ 32 ], who reported that among other ACE inhibitors, perindopril exerts outstanding antioxidant effects in various body tissues. Ancion et al [ 33 ] attributed the antioxidant effects of perindopril to its ability to decrease angiotensin II levels, thereby reducing ROS production.…”
Section: Discussionmentioning
confidence: 99%